Ginsenosides in Ovarian Cancer Therapy: Mechanistic Insights with an Emphasis on microRNA Regulation and Translational Prospects - Sobhan Jalali; Mohammadreza Besharatloo; Mojtaba Zehtabi; Dorrin Alipour Amini; Amir Hossein Barjasteh; Mohammad Hossein Pourhanifeh (Current Medicinal Chemistry, 2026)
Abstract: Ovarian cancer remains one of the most lethal gynecological malignancies due to late diagnosis, high recurrence rates, and resistance to conventional therapies. Emerging evidence underscores the therapeutic potential of natural compounds, among which ginsenosides, the principal bioactive components of ginseng, exhibit remarkable anticancer properties. This review summarizes current insights into the anti-ovarian cancer activities of ginsenosides, with particular focus on their regulatory effects on non-- coding RNAs, especially microRNAs. Ginsenosides modulate diverse molecular pathways, including apoptosis induction, autophagy regulation, epithelial-to-mesenchymal transition suppression, angiogenesis inhibition, and epigenetic reprogramming. Increasing evidence demonstrates that ginsenosides exert tumor-suppressive effects by restoring tumor-suppressor microRNAs and repressing oncogenic ones, thereby interfering with cancer stem cell maintenance, metabolic reprogramming, and metastatic progression. Furthermore, ginsenosides enhance the efficacy of chemotherapeutic agents such as paclitaxel and cisplatin while reducing associated toxicity. Despite promising preclinical findings, clinical translation remains limited due to challenges in bioavailability and pharmacokinetics. Collectively, ginsenosides represent a promising class of phytochemicals for ovarian cancer treatment, particularly through microRNA-centered mechanisms, warranting further investigation into optimized formulations, nanodelivery systems, and well-designed clinical trials.